Exploring the barriers to Pap smear test in Iranian women: a qualitative study - Tayebeh Marashi; Seyed Fahim Irandoost; Javad Yoosefi Lebni; Goli Soofizad (BMC, 2021)
Abstract Background Cervical cancer is one of the most frequent types of cancer in females. The Pap smear is one of the most essential ways of diagnosing and screening for this malignancy, and any failure can be caused by a number of causes. The current study sought to investigate barriers to Pap smear in Iranian women. Method This qualitative content analysis study was conducted in Iran in 2019. Data was gathered through focus groups and individual semi-structured interviews with 32 women and health professionals. The interviewees were chosen using a combination of purposive and theoretical sampling. The data was then analyzed using the content analysis approach developed by Graneheim and Lundman. Guba and Lincoln's criteria for establishing trustworthiness were explored. Results Data analysis resulted in the identification of four primary categories, seventeen subcategories, and 186 original concepts. The main categories include weakness of health system, difficult accessibility, low health literacy, and socio-cultural factors. Conclusion By informing women about the necessity and importance of Pap smear, providing the conditions, facilities, and equipment to facilitate the testing process, and paying more attention to cultural and social factors in cervical cancer and Pap smear planning, interventions, and policies, barriers to Pap testing can be eliminated.